Lipid nano scale cargos for the protection and delivery of food bioactive ingredients and nutraceuticals. (April 2018) - Akhavan, Sahar; Assadpour, Elham; Katouzian, Iman; Jafari, Seid Mahdi
Abstract: Background: The encapsulation and liberation technologies for bioactive food ingredients has opened the door to innovative and significant applications in food, nutrition, and pharmaceutical fields via the employment of nanotechnology. Coating materials in the formulation of nanocapsules are mostly lipid, carbohydrate or protein-based. The nanoencapsulation procedure in the food and nutraceutical areas involves the incorporation of natural ingredients, such as volatile additives, polyphenols, aromas, colors, vitamins, enzymes, oils and antimicrobial compounds in nano-sized capsules, providing the opportunities for higher stability and retention for the sensitive molecules against decomposition and loss of nutritional value during the production process or delivery along with offering a sustained release. Scope and approach: This review highlights the most recent nanoencapsulation advancements along with the formulations mainly based on lipid components; i.e., nanoemulsions, nanoliposomes and nanostructured lipid carriers in terms of preparation strategies, their classes, composition, attributes, analysis techniques, worked examples, and implementation in functional foods along with their upcoming evolution and future trends. Key findings and conclusions: Nanocapsules with lipid formulations are possible alternatives to micro-sized carriers owing to the enormous surface area and the following features which they offer, such as improved solubility, high bioavailability and establishment of sustained liberation of the nanoencapsulated food constituents and nutraceuticals. Graphical abstract: Schematic illustration of three important nanostructured lipid-based encapsulation formulations: nanoliposomes (A), nanoemulsions (B), and NLCs and SLNs (C). Highlights: Nanoencapsulation of nutraceuticals involves particles with 1–1000 nm diameters. Lipid-based nanoencapsulation systems are among the most promising technologies. Nanoliposomes, nanoemulsions, and nanostructured lipid carriers are explained. Digestion and bioavailability of lipid nano compartments are discussed.